INKORPORASI PERSPEKTIF GENDER DALAM PENGEMBANGAN REKAYASA ALAT DAN MESIN PERTANIAN - RITA NUR SUHAETI; SRI SUHARNI SIWI (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2004)
Incorporation of Gender Perspective in Agricultural Machinery Engineering. Development isbasically gender neutral. However, gender bias often occurs in the developmentimplementation and it leads to gender inequity and gender inequality. This implies that onlyone gender side (mostly men) accesses and takes a part in the various development programs,including agricultural development. In addition, they also control and benefit its output andoutcomes. In this reform era, agricultural sector still plays an important role in the Indonesia’seconomy. Agribusiness and smallholders would be successful if all discrimination forms foragribusiness agent’s empowerment is eradicated and market mechanism fairness could beserved. Due to cultural bias existence, roles of women in economic aspects are often takenfor granted. Therefore, dissemination of Republic Indonesia’s Act No 7/1984 especially inthe articles 11 and 14 to all stakeholders responsible for agricultural developmentimplementation in various sectors at rural areas is required so that that woman would benefitfrom labor saving technology skill. Social and institutional constraints should be overcome, inorder that woman farmers needs skill on operating and repairing simple agriculturalmachineries to lighten they daily drudgery.